Analysis of Narrative Writing Skills Among Junior High School Students in Indonesia - Yulianti, Yulianti; Umar, Umar; Sudewi, Putu Wahyu; Isma, Adi (Universitas Sulawesi Barat, 2024)
Writing is a critical skill for English language learners, enabling them to express ideas effectively. This study investigates the narrative writing abilities of second-grade students at SMPN 5 Wonomulyo, Indonesia, focusing on five key aspects: content, organization, vocabulary, language use, and mechanics. Employing a mixed-method approach, data were collected through writing tests and teacher interviews. The findings reveal that a majority of students (60%) failed to meet the minimum standard of writing proficiency. Content and vocabulary were identified as the most challenging aspects, with many students struggling to generate coherent ideas and use appropriate language. Interviews with the teacher highlighted contributing factors, including limited vocabulary, lack of practice, and reliance on conventional teaching methods. The study emphasizes the need for innovative, student-centered approaches to enhance narrative writing skills, such as collaborative writing exercises, peer feedback, and digital storytelling tools. Vocabulary enrichment and regular writing practice are also critical for improving performance. This research contributes to the body of knowledge on EFL writing and offers practical recommendations for improving teaching practices.